Comment on “The construction of ecological socialism under the concept of liberating nature: William Rice’s critique of the concept of controlling nature” - Zheng Huang (Trans/Form/Ação)
Commented article: LI, X. G. The construction of ecological socialism under the concept of liberating nature: William Rice’s critique of the concept of controlling nature. Trans/Form/Ação: Unesp journal of philosophy, vol. 48, n. 3, e025030 “Eastern thought”, 2025. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16015.